The influence of formal trade agreements and informal economic cooperation on international tourism flows. (December 2016) - Saayman, Andrea; Figini, Paolo; Cassella, Silvio
This article aims to contribute to the literature on the effects of trade bloc formation and plurilateral economic cooperation on international tourism flows. This research expands previous findings in the number of countries (58) and types of agreements (formal and informal, global and regional) under investigation in order to (i) capture the effect of both formal trade agreements and plurilateral economic integration on bilateral tourism flows; (ii) test the robustness of previous findings through the use of alternative econometric specifications, estimation techniques and measurement of tourism flows. In this respect, an important feature of this research is the introduction of 'total tourism', corresponding to the 'total trade' variable in trade studies, as an alternative dependent variable in the specification of the gravity model used throughout the article.